2020
DOI: 10.3390/ncrna6030035
|View full text |Cite
|
Sign up to set email alerts
|

Non-Coding RNA Databases in Cardiovascular Research

Abstract: Cardiovascular diseases (CVDs) are of multifactorial origin and can be attributed to several genetic and environmental components. CVDs are the leading cause of mortality worldwide and they primarily damage the heart and the vascular system. Non-coding RNA (ncRNA) refers to functional RNA molecules, which have been transcribed into DNA but do not further get translated into proteins. Recent transcriptomic studies have identified the presence of thousands of ncRNA molecules across species. In humans, less than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 100 publications
0
9
0
Order By: Relevance
“…In the recent years, we and others have demonstrated that miRNAs have an instrumental role in apoptosis and in the pathogenesis of myocardial disorders [1,[46][47][48][49][50][51][52] (Figure 1).…”
Section: Mirnas and Cardiomyocyte Apoptosismentioning
confidence: 99%
“…In the recent years, we and others have demonstrated that miRNAs have an instrumental role in apoptosis and in the pathogenesis of myocardial disorders [1,[46][47][48][49][50][51][52] (Figure 1).…”
Section: Mirnas and Cardiomyocyte Apoptosismentioning
confidence: 99%
“…Dysregulation of miRNA expression has been described in a variety of diseases, [ 14 17 ] particularly in cancers, [ 18 ] including HNSCC. [ 19 ] Increasing evidence has shown that miRNAs play an important role during HNSCC initiation and progression.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, a thorough analysis of the changes in the gene expression pattern is required to understand the morphological and functional modifications observed in diverse pathological and clinical conditions, which highlights the contribution of the studies reported in this article collection regarding vessel remodeling induced by drastic hemodynamic changes, by Zhang X. et al in an aortic constriction model and Jie et al in an arteriovenous fistula model. Likewise, in agreement with the relevance of the fine control of gene expression in vascular homeostasis, regulatory NcRNA, such as long non-coding RNAs (lncRNA) and microRNAs (miRNA), have been recognized to be key players in the control of endothelial and smooth muscle cell function (Balamurali and Stoll, 2020 ; Ono et al, 2020 ). Accordingly, NcRNAs have been found to be involved in the pathogenesis of several cardiovascular diseases, but also, they have been proposed as therapeutic target molecules, in line with the results presented in the articles of Cheng et al in spine cord injury repair and Su et al in diabetic neointimal hyperplasia.…”
mentioning
confidence: 83%